An assessment of the role of Doppler ultrasound velocity waveform analysis of the umbilical artery in the diagnosis of fetal distress in labour - Stuart, Ian Peter (Department of Obstetrics and Gynaecology, 2018)
Introduction: An assessment of the role of Doppler ultrasound velocity waveform analysis of the fetal umbilical arteries in the diagnosis of fetal distress in labour is made from a review of the literature and clinical study. Study objectives: 1) To determine the value of screening with Doppler ultrasound in high-risk labours in the prediction of the development of indicators of fetal distress. 2) To determine whether Doppler velocimetry indices of the umbilical arteries change with the development of indicators of fetal distress in labour. Design: Repeated Doppler velocimetry in selected high risk labours. Setting: Groote Schuur Hospital, Cape Town, South Africa, a large tertiary referral centre. Subjects: Thirty six women with singleton pregnancies complicated either by gestational proteinuric hypertension or by intrauterine growth retardation or both with a normal cardiotocographic tracing at the onset of labour. Main outcome measures: 1) Acid-base status of the fetus was assessed after deli very by analysis of umbilical artery blood. 2) Apgar score was recorded at 1 and 5 minutes. 3) Neonates were carefully examined for clinical signs of perinatal hypoxia. Results: Twenty seven fetuses were followed through labour. No relation was found between umbilical artery Pourcelot ratio (resistance index) on admission in labour and umbilical artery base deficit. Six fetuses were born with an umbilical artery base deficit of more than 10 mmol 1-1. Zero change in mean Pourcelot ratio was noted in both normal and acidotic fetuses. None of the acidotic fetuses showed a change in Pourcelot ratio of more than 0.03. The study had an 80% power to detect a change in mean Pourcelot ratio of 0.07 in the normal fetuses and 0.16 in the acidotic fetuses at a 95% confidence level. No relation was found between Pourcelot ratio on admission in labour or change in Pourcelot ratio during labour and Apgar score. None of the neonates showed clinical signs of perinatal hypoxia. Conclusions: Doppler velocimetry of the umbilical arteries in labour as measured by the Pourcelot ratio does not contribute to the diagnosis of fetal distress in labour.